Blockchain In Islamic Finance: A Review Using Bibliometric Approach - Matondang, Desy Mayasari; Simanjuntak, Windi Wahyuni; Siregar, Deni Afnita; Siregar, Budi Gautama; Rusydiana, Aam Slamet (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study reviews research on the theme of blockhain in Islamic finance with leading journals. This study uses bibliometric analysis of 161 selected articles related to blockchain in Islamic finance published by national and international journals derived from the dimension database. The entire sample of journal publications has been published in eight years from 2017 to 2024. There are 12 authors with research results dominated by the United States and Malaysia, followed by Qatar. Then data processing is carried out by analysing using the VosViewer application which aims to determine the bibliometric map of blockhain research development in Islamic finance in the world. Furthermore, based on bibliometric keyword mapping, there are 3 clusters that can become research paths with topics related to blockhain in Islamic finance. Furthermore, the emergence of blockhain in Islamic finance is expected to provide significant improvements in transparency and accountability in the Islamic financial sector. The implications include the potential to strengthen public trust and efficiency in Islamic financial management, while facing challenges in sharia compliance and technological adaptation.